2017
DOI: 10.4103/0971-5851.203514
|View full text |Cite
|
Sign up to set email alerts
|

Profile of primary pediatric brain and spinal cord tumors from North India

Abstract: Background and Objective:The study was carried out to find the profile of pediatric brain and spinal cord tumors during 2006–2015 in a tertiary referral center of North India.Materials and Methods:It was a retrospective medical record-based observational study. All children <18 years of age with confirmed histopathological diagnosis of cancer were included in the study.Results:Central nervous system (CNS) tumors constituted 5.6% of all pediatric solid malignancies in our hospital. A total of 54 brain tumors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
6
7
0
1
Order By: Relevance
“…Regarding the location of brain tumors, a frequency of posterior fossa tumors was found in 22.4%, which is similar to that reported by Ostrom et al 7 , whose five most frequent locations were: cerebellum, with 18.5%; other brain regions, with 15.2%; brainstem, with 12.4%, followed by pituitary and craniopharyngeal duct (8.1%) and cranial nerve tumors (7.5%). As regards histological variants, Azad et al 14 reported that the most common was ependymoma, with 19.4%, followed by pilocytic astrocytoma and medulloblastoma with 16.7% each, while, in our findings, the most common was medulloblastoma with 22.4%, followed by pilocytic astrocytoma and neuroectodermal tumor with 16.5% and 8.2%, respectively; similarly, Shirazi et al 19 found medulloblastoma (n = 11, 20.37%) to be the most common neoplasm. In turn, Zhou et al 20 , in their study carried out in China with 1,485 cases, found astrocytoma (31%), craniopharyngioma (18%), medulloblastoma (15%), germ cell tumors (8%) and ependymal tumors (6%) to be the most common CNS tumors.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding the location of brain tumors, a frequency of posterior fossa tumors was found in 22.4%, which is similar to that reported by Ostrom et al 7 , whose five most frequent locations were: cerebellum, with 18.5%; other brain regions, with 15.2%; brainstem, with 12.4%, followed by pituitary and craniopharyngeal duct (8.1%) and cranial nerve tumors (7.5%). As regards histological variants, Azad et al 14 reported that the most common was ependymoma, with 19.4%, followed by pilocytic astrocytoma and medulloblastoma with 16.7% each, while, in our findings, the most common was medulloblastoma with 22.4%, followed by pilocytic astrocytoma and neuroectodermal tumor with 16.5% and 8.2%, respectively; similarly, Shirazi et al 19 found medulloblastoma (n = 11, 20.37%) to be the most common neoplasm. In turn, Zhou et al 20 , in their study carried out in China with 1,485 cases, found astrocytoma (31%), craniopharyngioma (18%), medulloblastoma (15%), germ cell tumors (8%) and ependymal tumors (6%) to be the most common CNS tumors.…”
Section: Discussionsupporting
confidence: 84%
“…[ 1 2 3 ] There are not many studies from India which have looked into the epidemiology of pediatric brain tumors and compared it with data from the rest of the world. [ 4 5 6 7 8 9 10 11 12 ] Since this is a hospital-based study, it may not reflect the true epidemiology of the tumors, but nevertheless, it is the first attempt of its kind from Kerala. The aim of this study was to analyze the epidemiology of pediatric brain tumors in North Kerala and compare it with data from the rest of India and other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Central nervous system tumors are the most common solid tumors and the most important cause of cancer death in pediatric patients [9]. Low-grade and high-grade astrocytomas are one of the most common primary pediatric brain tumors [10]. Although pediatric brain tumors differ from adult tumor, the same treatment protocol is applied.…”
Section: Discussionmentioning
confidence: 99%